Perfil epidemiológico de las pacientes hospitalizadas en el servicio de Gineco-obstetricia del Hospital General Isidro Ayora de Loja - Villavicencio Acaro, Katiuska Lizbeth (2023)
Obstetrics and gynecology pathologies are a public health problem that, according to data mentioned by the WHO (World Health Organization), have increased in recent years, among which premature rupture of membranes, anemia and cesarean delivery stand out the most, and pregnancy monitoring has become more relevant. The objective of this research was to analyze the epidemiological profile of patients hospitalized in the gynecological-obstetrics service of the Isidro Ayora de Loja General Hospital during the period October-December 2021. The study was a descriptive, quantitative, cross-sectional study with correlational scope. A data collection form was used as an instrument to collect information from 148 medical records that met the inclusion criteria. The data were processed in the SPSS version 2.2 statistical program. The findings obtained in relation to the sociodemographic characteristics showed that 48% were young women, 56.5% were housewives, 47.3% had a high school education, and 54.5% were single. With respect to the epidemiological profile, 26.4% of the women had a diagnosis of pregnancy supervision, followed by 19.4% and 16.9% with diagnoses of cesarean delivery and premature rupture of membranes, respectively. The results were socialized through the presentation of the final report of the project in the study area. Finally, it is concluded that the results obtained in relation to the epidemiological profile are in agreement with those reported in the literature, highlighting the diagnoses of pregnancy supervision, cesarean delivery and premature rupture of membranes